2001
DOI: 10.1086/318280
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a Series of X‐Ray Dips Associated with a Radio Flare in GRS 1915+105

Abstract: We report the detection of a series of X-ray dips in the Galactic black hole candidate GRS 1915+105 during 1999 June 6−17 from observations carried out with the Pointed Proportional Counters of the Indian X-ray Astronomy Experiment on board the Indian satellite IRS-P3. The observations were made after the source made a transition from a steady low-hard state to a chaotic state which occuered within a few hours. Dips of about 20−160 seconds duration are observed on most of the days. The X-ray emission outside t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 22 publications
5
29
0
Order By: Relevance
“…These dips are also seen in class θ light curves. During a major portion of the huge radio flares associated with superluminal blob emission a series of soft dips are present (Naik et al 2001). Mirabel & Rodriguez (1999) have pointed out that in each epoch of this type of outflow, the mass condensation is around 10 23 g. In order to achieve this, we require that matter is accumulated from disk evacuation at each "dip" and within each epoch, successive mini-blobs move faster than the earlier blob in order to "catch up".…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These dips are also seen in class θ light curves. During a major portion of the huge radio flares associated with superluminal blob emission a series of soft dips are present (Naik et al 2001). Mirabel & Rodriguez (1999) have pointed out that in each epoch of this type of outflow, the mass condensation is around 10 23 g. In order to achieve this, we require that matter is accumulated from disk evacuation at each "dip" and within each epoch, successive mini-blobs move faster than the earlier blob in order to "catch up".…”
Section: Resultsmentioning
confidence: 99%
“…This may indicate some other runaway process with a longer time scale of tens of days. Naik et al (2001) have observed such X-ray dips at a rate of once in a few hundred seconds during the peak or the radio flare. If there are ∼1000 evacuation events during an episode of superluminal blob ejection (in a few days), then total mass condensation would be 10 23 g. Hence in order to explain the observation of Mirabel & Rodriguez (1999), one must require that in each epoch, matter is accumulated from at least a thousand evacuation events.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations